KEMATIAN FILOSOFIS MENURUT ANTROPOLOGI METAFISIKA ANTON BAKKER - Ardi, Mulia (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2019)
This article tries to analyze the phenomena of the death philosophically the perspective of the Anton Bakker?s anthropology of the metaphysics. The death events encountered by humans in daily life according to Bakker can be traced through two perspectives, namely negative or positive views. Negative views regard death as the end of everything. Death is the culmination (final) that completes all episodes of human life. There is nothing left behind death. Humans are fully considered complete and finished. Conversely, in a positive view, death is accepted by humans as a new phase of eternity. Death, in this case, does not divert or alienate people from the world. Humans stay alive and don't leave the world. Death crystallizes and perpetuates all human life. Through his death, humans are actually born as new humans in the world. Keywords: Death, Negative Views, Positive Views.